Analysis of Community Trust Formation Agains UPN “Veteran” East Java - Muslimin; H. Pudjo (Nusantara Science and Technology Proceedings)
At present the study of factors influencing public trust in Higher Education in Indonesia has received enough attention from researchers to conduct a more in-depth study so that decisions taken by Higher Education are on target. Therefore, the trust of the public as consumers of Higher Education services is an important thing that needs to be known by the Higher Education with the aim of knowing what things are affecting people's trust in loyalty to UPN College "Veteran" East Java. UPN "Veteran" East Java must continue to improve the quality of its academic services so that public trust will increase so that it will generate a strong sense of loyalty towards UPN "Veteran" East Java. The following study intends to discuss the continued importance of Brand characteristics, Company characteristics and Consumer brand characteristics in shaping public trust in loyalty to UPN "Veteran" East Java. The population in this study were all prospective students of the University of National Development "Veteran" East Java who registered through an independent path. The sampling technique used in this study is a probability sampling technique where each element of population has the same opportunity to become a sample. While the method used is the stratified proportional random sampling method, the sample in this study were prospective independent students of UPN "Veteran" East Java, Data analysis was carried out by using the component-based SEM method using PLS chosen as an analytical tool in this study. The results of this study indicate that Brand characteristics, Company characteristics and Consumer brand characteristics contribute to Loyalty towards UPN "Veteran" East Java.